Optimizing Financial Management to Improve Regional Performance - Jaja Jaja; Fernandes Simangunsong (Universitas Muhammadiyah Ponorogo, 2027)
This study analyzes strategies for optimizing local financial management through the strengthening of good governance within the framework of Public Financial Management (PFM) to improve the financial performance of the West Bandung Regency (KBB) government. The research background is based on low fiscal autonomy, reflected in the contribution of Local Own-Source Revenue (PAD) of around 18–24% and high dependence on central government transfers (±75–77%), resulting in limited fiscal discretion and making it difficult to transform public spending into measurable public value. The study employs a qualitative approach using a case study design, involving cross-actor interviews (Bappelitbangda, BKAD, Inspectorate, OPD, academics), a review of financial management cycle documents (from planning to accountability/LKPD), and triangulation of sources, techniques, and time. The research findings indicate that the process has proceeded in accordance with regulations; however, the leverage over the fiscal structure is determined by substantive governance: the validity of planning data, the consistency of documents and audit trails, internal controls from the outset, and cross-OPD coordination. Performance from 2020 to 2024 improved managerially (PAD effectiveness >100%, SiLPA decreased) but PAD remains small and operational expenditures are dominant (±67–70%). The SWOT analysis places KBB in Quadrant III (IFAS 2.40; EFAS 2.47), so a turnaround strategy is prioritized through a package of data governance, quality assurance, change control/document locking, a single source of truth, and a learning loop for oversight findings. Keyword: Regional Financial Management; Good Governance; PFM; Wo Strategy; Fiscal Autonomy; Local Revenue; Local Government Financial Performance;